MATRIKS TRANSFORMASI OPERATOR VECD* MENJADI VECH^ - Alsbaldo, Yuco; Yanita, Yanita; Yulianti, Lyra (LPPM Universitas Bina Bangsa, 2025)
This article discusses a new matrix operator that is constructed differently from the vech operator and the vecd operator by stacking the main diagonal entries (supra-diagonal) and entries of a square matrix. This operator, called operator, explicitly constructs a matrix that transforms into , where is an square matrix, and then obtains the properties of the transformation matrix